Agri-Food Industry and Environmental Impact to Ensure Sustainable Development. Factors and Threats’ Awareness in the Post-Pandemic Period - KASHAKOVA, Gulnar; AIMURZINOV, Murat; YEGINBAYEVA, Akzhan; MIZAMBEKOVA, Zhamilya; KHAMITOVA, Dariga; NAKIPOVA, Gulmira (Journal of Environmental Management and Tourism; Vol 13 No 7 (2022): JEMT, Volume XIII, Issue 7(63), Winter 2022, 2022)
The purpose of this study is to analyze the theoretical insights and formulate recommendations for improving the agro-food industry and its impact on the environment to ensure sustainable development, as well as to consider the factors and awareness of threats in the post-pandemic period. The analysis will allow to establish some conclusions about competitiveness and dependence of agro-food security of the countries as well as to identify the risks that hinder the effective functioning of the agro-industrial sector, as well as to make predictive values by building a trend model. Also, a complex of factors and key-challenges will be approached with the scope to awareness the environmental impact for a sustainable development of our society.